2015
DOI: 10.1186/s40623-015-0192-4
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of medium-scale traveling ionospheric disturbances using SuperDARN Hokkaido ground backscatter data for 2011

Abstract: We describe an automated technique to determine parameters of traveling ionospheric disturbances (TIDs) using the Super Dual Auroral Radar Network (SuperDARN) high frequency (HF) radar data. The technique is based on the analysis of minimum ground backscatter range variations corresponding to different radar beams. Using this technique, we processed the SuperDARN Hokkaido radar data for 2011 and revealed statistical distributions of medium-scale TID (MSTID) azimuth and apparent horizontal velocity. We found fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
3

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 28 publications
(48 reference statements)
4
30
0
3
Order By: Relevance
“…8. Oinats et al (2015) also observed southwest azimuths in the summer, equinox nighttime, and equinox evening and northwest azimuths in summer daytime and evening; similar observations are not found in our observations from Taiwan. Otsuka et al (2013) studied MSTIDs over Europe using GPS in 2008.…”
Section: Resultssupporting
confidence: 30%
See 2 more Smart Citations
“…8. Oinats et al (2015) also observed southwest azimuths in the summer, equinox nighttime, and equinox evening and northwest azimuths in summer daytime and evening; similar observations are not found in our observations from Taiwan. Otsuka et al (2013) studied MSTIDs over Europe using GPS in 2008.…”
Section: Resultssupporting
confidence: 30%
“…They found that a majority of MSTIDs propagated equatorward in this period, which is similar to our observations. Oinats et al (2015) studied MSTIDs using the Super Dual Auroral Radar Network in Hokkaido, i.e., a location that is more poleward than Taiwan. Northeastward propagating MSTIDs were typical for summer and equinox.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The steps of data processing and analysis are almost the same as described in Oinats et al (2015). Here, we list them briefly and emphasize the differences between present and previous techniques.…”
Section: Data Processingmentioning
confidence: 93%
“…In case of the absence of the elevation measurement, the effective height is usually assumed to be fixed at a specific value (Bristow et al 1994;Grocott et al 2013;Oinats et al 2015), or some empirical height models could be used Yeoman et al 2008). Figure 2a shows the dependence of the effective reflection height calculated using Eq.…”
Section: Application Of the Calculated Characteristicsmentioning
confidence: 99%